PENGEMBANGAN DATA WAREHOUSE DAN ON-LINE ANALYTICAL PROCESSING (OLAP) UNTUK PENEMUAN INFORMASI DAN ANALISIS DATA (Studi Kasus : Sistem Informasi Penerimaan Mahasiswa Baru STMIK AMIKOM PURWOKERTO) - Giat Karyono (Telematika, 2011)
Background preparation of this thesis report, Silva (2007) mentions that the competition for students between universities was inevitable as it grows, universities should equip themselves to survive in the competition that ultimately colleges that are not sensitive to compete. The demand for a high performance organization that has also faced by STMIK AMIKOM Purwokerto. Existing data on the colleges that are so big and much needed storage space allocation will be helped and be efficient with the data warehouse (Wikramanayake, 2006). Based on the data management / decision makers in education institutions is always a constant attempt to find an information / decision analysis that are useful in the search for new students. For the needs of the analysis method was used OLAP (OnLine Analytical Processing) which presents the data in the form of multidimensional query that is easier to be presented and analyzed.Data collection methods used in the preparation of this report include the method of observation of interviews and field studies, literature, internet search, as well as observing systems that are already running.This research was conducted with the following steps: 1) The analysis system that includes the current SIPMB analysis, identification of the cause of the problem, analysis of system requirements. 2) System design, including design of data warehouses and OLAP applications PMB. This design produces data warehouse architecture, data modeling dimensional, the establishment of a data warehouse, OLAP stakeholders PMB, PMB OLAP viewpoint, scenario, model systems, and user interface design. 3) Implementation, covers the application of OLAP applications PMB and operations performed included, 4) testing system, test the product in accordance with ISO 9126 software includes six quality characteristics of Functionality, Reliability, Usability, efficiency, Maintainability, Portability. In order not to interfere the performance of the operational databases (OLTP) SIPMB process of creating a data warehouse is done on different machines by performing replicate of the database used SIPMB. For the needs of the application is made data analysis OLAP PMB. These applications could present multidimensional data in grid view. Analysis of these data may include analysis of specialization in new student enrollment based on the period of new admissions, enrollment surge, home school, home province and district, Pengembangan Data Warehouse dan On-line Analytical Processing (OLAP) Untuk Penemuan Informasi Dan Analisis DataJurnal Telematika Vol. 4 No.2 Agustus 2011 14registration information, day, month, or year. So that the results of data analysis can be the management in determining the appropriate marketing strategies to increase the number of freshmen applicants either currently running or for admission in the coming year.